The bright sword : [large type] a novel of King Arthur - Grossman, Lev (Thorndike Press, a part of Gale, a Gengage Company, 2024)
"A gifted young knight named Collum arrives at Camelot to compete for a spot on the Round Table, only to find that he's too late. The king died two weeks ago at the Battle of Camlann, leaving no heir, and only a handful of the knights of the Round Table survive. They aren't the heroes of legend, like Lancelot or Gawain. They're the oddballs of the Round Table, from the edges of the stories, like Sir Palomides, the Saracen Knight, and Sir Dagonet, Arthur's fool, who was knighted as a joke. They're joined by Nimue, who was Merlin's apprentice until she turned on him and buried him under a hill. Together this ragtag fellowship will set out to rebuild Camelot in a world that has lost its balance. But Arthur's death has revealed Britain's fault lines. God has abandoned it, and the fairies and monsters and old gods are returning, led by Arthur's half-sister Morgan le Fay. Kingdoms are turning on each other, warlords lay siege to Camelot and rival factions are forming around the disgraced Lancelot and the fallen Queen Guinevere. It is up to Collum and his companions to reclaim Excalibur, solve the mysteries of this ruined world and make it whole again. But before they can restore Camelot they'll have to learn the truth of why the lonely, brilliant King Arthur fell, and lay to rest the ghosts of his troubled family and of Britain's dark past."--